Globalization, political economy, business and society in pandemic times - Ghauri, Pervez; Fang, Tony; Hassler, John (International business and management series ;, 2021)
Globalization, Political Economy, Business and Society in Pandemic Times is a product of the 5th Emerging Markets Inspiration Conference (EMIC) at Stockholm University during May 14-15, 2020. The purpose of the book is to arrive at a holistic understanding of the impact of the COVID-19 pandemic on politics, economies, business, and society in a globalized world. The scientific community acted swiftly to study COVID-19 and its various possible societal correlations. This edited collection contributes to the growing literature on COVID-19 through a multidisciplinary approach by addressing both macro and micro issues from both local and global angles in both critical and self-critical tones.